A Review of Unmanned Aerial Vehicle (UAV) Applications In The Road Surveying - BIN MAHASSAN, SYAHMIN NASRULLAH; Sarif, Abd Sukor (Progress in Engineering Application and Technology, 2021)
Road transport is a must as it provides ample facilities benefits to a countryand to individuals, especially in improving access to places jobs, economic resources,educational facilities, health centers and more. Behind the importance oftransportation to the population, there is also a negative effect, namely, roadaccidents. The cause of an accident can be done by various factors. One of thosefactors is road design. This paper presents a review of recent developments in relationto the application of UAVs in three major domains of transportation, namely; roadsafety, traffic monitoring and highway infrastructure inspection. This study, includesdata collection, data analysis, and results. Advance application of UAVs in extractingkey information which will be utilized in accident investigation and assessment,traffic flow analysis and damage assessment roads. To further enhance the knowledgeof the advantages of this UAV. In addition, the private sector especially needs to applythe use of this UAV for their company to increase the skilled manpower for the useof this UAV while accelerating all the processes that will be carried out especially inthe surveying sector.